Investigation of antinociceptive, antipyretic, antiasthmatic, and spasmolytic activities of Brazilian Cannabis sativa L. roots in rodents. (5th October 2021) - Menezes, Pedro Modesto Nascimento; Araújo, Tarcísio Cícero de Lima; Pereira, Emanuella Chiara Valença; Neto, Janaine Almeida; Silva, David Souza; Brito, Mariana Coelho; Lima, Kátia Simoni Bezerra; Monte, Alane Pains Oliveira do; Matos, Maria Helena Tavares de; Lima, Ricardo Santana de; Ribeiro, Luciano Augusto de Araújo; Silva, Fabrício Souza; et al.
Abstract: Ethnopharmacological relevance: Many studies are performed with the aerial parts of Cannabis sativa L. (Cannabaceae). However, roots remain poorly studied, despite citations in the scientific literature. The C. sativa roots are indicated for the treatment of pain, inflammation, fever, among other health problems. Aim of the study: This study aimed to evaluate the antinociceptive, antipyretic, antiasthmatic, and spasmolytic activities of C. sativa roots in experimental models using mice and rats. Material and methods: The chemical composition of the aqueous extract of C. sativa roots (AECsR) was evaluated by LC-MS. The antinociceptive activity was assessed in mice by the induction of writhing with acetic acid, paw licking with formalin, and reactivity in the hot plate test. Fever was induced by the administration of a suspension of Saccharomyces cerevisiae in young rats. The asthmatic activity was performed with ovalbumin (OVA)-immunized mice with cellular and histological analysis. Finally, the spasmolytic activity was performed using mice isolated trachea. For in vivo studies, the doses were 12.5, 25, or 50 mg/kg whereas for in vitro, the concentration of AECsR was 729 μg/mL. Results: From the LC-MS data, we identified p -coumaroyltyramine, feruloyltyramine canabissativine in AECsR. The extract promoted a reduction of writhing in all tested doses (12.5, 25, or 50 mg/kg). Similarly, it reduced the pain in the formalin test at doses of 12.5 and 50 mg/kg (first phase) and 12.5 and 25 mg/kg (second phase). In the hot plate test, the doses of 12.5, 25, and 50 mg/kg promoted antinociceptive effect at different times, and the lowest dose maintained its action in the analyzes performed at 60, 90, and 120 min after administration. The anti-inflammatory activity of AECsR was observed in the mouse model of asthma, reducing the total leukocyte count in the bronchoalveolar fluid (BALF) at a dose of 25 mg/kg, as well as reducing eosinophilia in all tested doses (12.5, 25, and 50 mg/kg). Histological analysis of lungs stained with H&E and PAS showed a reduction in the number of inflammatory cells in the perivascular and peribronchial region, as well as reduced mucus production. Conclusion: The results suggest that AECsR promotes pain control, either by a central or inflammatory mechanism, and has antiasthmatic activity. However, there was no antipyretic or spasmolytic effect. Graphical abstract: Image 1 Highlights: p -coumaroyltyramine, feruloyltyramine, and cannabissativine were identified in C. sativa roots. C. sativa roots have antinociceptive and anti-inflammatory activities. C. sativa roots showed antiasthmatic activity. C. sativa roots did not show antipyretic and spasmolytic activities.